Answer:
The solution of the equations are
So all the options are wrong.
Explanation:
We have
2x + y + 3z = 12 -------------------eqn 1
x – y + 4z = 5 -------------------eqn 2
–4x + 4y – 4z = –20 -------------------eqn 3
eqn 2 x 2
2x – 2y + 8z = 10 -------------------eqn 4
eqn 4 - eqn 1
2x – 2y + 8z - (2x + y + 3z) = 10 - 12
-3y +5z = -2 -------------------eqn 5
eqn 1 x 2
4x + 2y + 6z = 24 -------------------eqn 6
eqn 3 + eqn 6
–4x + 4y – 4z + 4x + 2y + 6z = -20 + 24
6y + 2 z = 4 -------------------eqn 7
eqn 5 x 2
-6y +10z = -4 -------------------eqn 8
eqn 7 + eqn 8
12 z = 0
z = 0
Substituting in eqn 7
6y + 0 = 4
Substituting in eqn 2
So the solution of the equations are
So all the options are wrong.